2005
DOI: 10.1111/j.1423-0410.2005.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative stimulation of erythropoiesis with intravenous iron and erythropoietin reduces transfusion requirements in patients with hip fracture. A prospective observational study

Abstract: The blood-saving protocol implemented seems to reduce ABT requirements in patients with HF, and is associated with a lower postoperative morbidity. The possible mechanisms involved in these effects are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 39 publications
3
107
1
4
Order By: Relevance
“…A review of the evidence based outcomes of the different supplementations in hip and knee surgery suggested that iron therapy, both oral and intravenous have been shown to reduce the need for allogeneic blood transfusion and significantly reduced the post-operative infection rate [28][29][30][31]. In our hand, IV iron was superior to oral iron and both have improved the preoperative Hb, nevertheless, with a greater and significant effect in the IV iron group.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A review of the evidence based outcomes of the different supplementations in hip and knee surgery suggested that iron therapy, both oral and intravenous have been shown to reduce the need for allogeneic blood transfusion and significantly reduced the post-operative infection rate [28][29][30][31]. In our hand, IV iron was superior to oral iron and both have improved the preoperative Hb, nevertheless, with a greater and significant effect in the IV iron group.…”
Section: Discussionmentioning
confidence: 57%
“…A systemic review comparing the evidence of administering erythropoietin with iron supplements to an active control group of either iron supplementation or cell salvage [26,30], showed that the clinical outcomes of post-operative infections, length of stay and 30 day mortality were generally not significant when compared to the active control group in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the 30 day mortality or the mean duration of hospitalization. 70 Previous recommendations that patients with preoperative anaemia due to iron deficiency or chronic disease may receive preoperative treatment with i.v. or oral iron, depending on the timing of surgery, the patient's tolerance of oral iron, and iron status, 71 72 are based on low-to-moderate-quality evidence.…”
Section: Patient Blood Managementmentioning
confidence: 99%
“…En cirugía, la experiencia se ha centrado con la corrección preoperatoria de la anemia por déficit de hierro debido a Optimización de la hemoglobina preoperatoria con hierro intravenoso 7 miomas 20 o neoplasia de colon 21 , o cirugía traumatológica y ortopédica 22,23 . En el campo de la cirugía ortopédica solo hay disponibles estudios observacionales con tamaños muestrales de 21 24 , 20 25 , y 21 26 pacientes.…”
Section: Discussionunclassified
“…La media de dosis de hierro recibida fue prácticamente idéntica que la que recibieron aquellos pacientes tratados únicamente con hierro iv y la dosis de rHuEPO fue de 2,4 inyecciones de 40.000 UI. La administración de hierro se ha utilizado también para mejorar la eficacia del tratamiento intravenoso con rHuEPO 23 . En un estudio que incluyó solo a 12 pacientes en los cuales se comparó la administración de 200 mg de hierro-sacarosa asociada a rHuEPO con la administración únicamente de hierro oral, Rohling et al 28 no observaron mejorías en la Hb preoperatoria.…”
Section: Discussionunclassified